The myth of the poor fisher : Evidence from the Nordic countries - Nielsen, Max; Asche, Frank; Bergesen, Ole; Blomquist, Johan; Henriksen, Edgar; Hoff, Ayoe; Nielsen, Rasmus; Viðarsson, Jónas R.; Waldo, Staffan (Marine Policy, 2018)
Fishers are often perceived to be poor, and low income levels are used to justify subsidies and other types of direct and indirect income support to maintain coastal communities. In this study fishers’ income levels are investigated in four Nordic countries; Denmark, Iceland, Norway and Sweden for different types of fishers and vessels and in comparison to alternative occupations. The most important result is that fishers in these countries are doing relatively well, and only in Sweden is the fishers’ average income level below the average national income. Within the fleets, there are substantial differences. Owners of coastal vessels tend to have the lowest income, and also lower than crews. Owners as well as crews on larger vessels tend to do much better and in the largest fishing nations, Iceland and Norway, they do especially well.